Innovative TEFL Methods: Enhancing Emotional Literacy in TEFL Learners through the Analysis of John Lennon’s Song ’Imagine’ - noveldi, Ochta; Absharini Kardena (BiCED Proceeding, 2024)
The development of emotional literacy is essential for fostering effective communication and enhancing language proficiency among second-language learners. This study addresses the question of how music, specifically John Lennon’s metaphor-laden song "Imagine," can be utilized as a tool to enhance emotional literacy in TEFL learners. This study investigates the use of John Lennon’s song lyrics with a specific focus on five TEFL learners enrolled in the FIES English Course. The novelty of this research lies in its integration of emotional literacy development within a TEFL framework through the analysis of song lyrics, providing a creative approach to language education. Employing a qualitative methodology, this study utilizes Interpretative Phenomenological Analysis (IPA) to explore learners' personal and social experiences with emotionally rich content. The participants, with varying proficiency levels, engaged in lyric analysis, group discussions, and reflective writing tasks. The findings reveal an expanded emotional vocabulary and an enhanced ability to express complex emotions in English. Additionally, the familiar and emotionally engaging content significantly increased learner motivation and participation in language lessons. These results suggest that integrating music with deep emotional themes into English learning can improve emotional awareness and communicative competence, offering a meaningful and innovative approach to TEFL.